2023
DOI: 10.1108/ijbpa-10-2022-0169
|View full text |Cite
|
Sign up to set email alerts
|

Quality management framework for government social housing construction in South Africa

Christopher Amoah

Abstract: PurposeIn addressing the housing deficits for the less privileged citizens, the South African government began constructing social housing after coming to power in 1994. However, the construction of these houses is bedevilled with many issues; prominent among them are poor quality of the constructed houses. This study seeks to develop a quality management framework for achieving quality and efficiency in public-sector housing construction, a hallmark of the country's procurement goals.Design/methodology/approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Abas et al [15] emphasized the importance of factors such as steady advancements, joint work, communication, the availability of technical personnel, ISO certification, and the contractor's procurement unit. In addition, the study Amoah [22] carried out for a housing project in South Africa revealed that the significant factors of poor-quality housing construction are related to project management. Quality management factors, including having a customer focus, making continuous improvements, applying strategic-based approaches, and utilizing total employee involvement, have been found to positively and significantly impact the performance of medium-sized construction projects [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abas et al [15] emphasized the importance of factors such as steady advancements, joint work, communication, the availability of technical personnel, ISO certification, and the contractor's procurement unit. In addition, the study Amoah [22] carried out for a housing project in South Africa revealed that the significant factors of poor-quality housing construction are related to project management. Quality management factors, including having a customer focus, making continuous improvements, applying strategic-based approaches, and utilizing total employee involvement, have been found to positively and significantly impact the performance of medium-sized construction projects [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the global solutions that have been adopted to promote sustainable-based construction risk management include a developed new interpretative framework for firms' risk management strategies analysis, comprehensive risk management function planning process, resilience and flexibility, supported with integrated mechanisms (Settembre-Blundo et al, 2021), risk assessment and vulnerability (Zhao, 2022;Cevikbas et al, 2024), risk management mitigation framework of a construction project in developing countries (Wang et al, 2004), innovative methodological tool via innovative organisational structures (Biron et al, 2021), a quality management framework for public-sector housing delivery (Amoah, 2023), holistic view of each type of risk and its impact on sustainability (Tsalis et al, 2020), technological turbulence (Foli et al, 2022), collaborative strategies (Cangemi et al, 2011;Manhart et al, 2020), and strengthen the relationship between risk management techniques and corporate sustainability evaluation in line with the 2023 Agenda (Tsalis et al, 2020). Whether these possible solutions have been considered by a few studies conducted in developing countries' context of improving construction risk management in turbulent times for possible implementation to enhance organisations sustainability is uncertain; hence, motivated the study.…”
Section: Introductionmentioning
confidence: 99%
“…, 2004), innovative methodological tool via innovative organisational structures (Biron et al. , 2021), a quality management framework for public-sector housing delivery (Amoah, 2023), holistic view of each type of risk and its impact on sustainability (Tsalis et al. , 2020), technological turbulence (Foli et al.…”
Section: Introductionmentioning
confidence: 99%